2017
DOI: 10.4103/2277-9531.204742
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the overcrowding in outpatient healthcare

Abstract: Background:The expansion of outpatient services and the desire to provide more outpatient care than inpatient care create some problems such as the overcrowding in the outpatient clinics. Given the importance of overcrowding in the outpatient clinics, this qualitative study aimed to determine the factors influencing the overcrowding in the specialty and subspecialty clinic of a teaching hospital.Materials and Methods:This was a qualitative study conducted in the specialty and subspecialty clinic of a hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Hospital adverse events increase with crowding, and have further effects on patient satisfaction, quality of nursing, treatment, wait time, and length of stay [ 1 – 4 ]. A vast literature about overcrowding focus on the outpatient wards [ 1 , 5 ] and emergence departments [ 4 , 6 ]. Overcrowding appearing in the inpatient wards should also be paid attention to.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital adverse events increase with crowding, and have further effects on patient satisfaction, quality of nursing, treatment, wait time, and length of stay [ 1 – 4 ]. A vast literature about overcrowding focus on the outpatient wards [ 1 , 5 ] and emergence departments [ 4 , 6 ]. Overcrowding appearing in the inpatient wards should also be paid attention to.…”
Section: Introductionmentioning
confidence: 99%
“…Wait times for outpatients and the management thereof is a major challenge to providing outpatient services, especially in large centers and hospitals. 26 Studying patient flow in the system will help identify the current status of the system and its bottlenecks and will play an important role in managing the delivery process and, ultimately, reducing wait times for patients. 1 Patient flow assessment results from the studied hospital indicated that more than 91% of a patient's total stay in the system was related to wait time, and more than 82% of total wait time was for physical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The patient flow data is basically time series data. In [48], a time series is defined as a vector X = {x (1) , x (2)…”
Section: Related Workmentioning
confidence: 99%
“…Overcrowding of hospital waiting rooms by patients characterizes the outpatient departments (OPDs) of healthcare centers of developing countries [1,2]. It is true that most of the patients that visit health centers have varying health challenges and some may require prompt medical attention.…”
Section: Introductionmentioning
confidence: 99%